Oxford international english student anthology level 1 - Miles, Liz (Oxford University Press London, 2017)
The Oxford International English Student Anthology is a curated collection of texts that exposes students to a variety of literary genres, enhancing their reading and comprehension skills through engaging stories, poems, and essays.